Limbah Cangkang Kepiting sebagai Biokoagulan pada Sistem Water Treatment (Kajian Pengaruh Variasi Jenis dan Konsentrasi Koagulan, Kecepatan Pengadukan) - Ani Melani; Robiah; Pandu Pratama (LPPM Politeknik Jambi, 2023)
Generates quite a lot of hard skin (shell) waste, the amount of waste can reach around 40-60% of the total weight of the crab. Crab shell waste contains chemical compounds, including 30-40% protein; 30-50% minerals and 50-70% Chitin. Chitin can be further processed to produce chitosan which has many benefits in various fields, one of benefits is as a coagulant. The purpose of this study was to determine the characteristics of the crab shell with SEM and FTIR test and its ability as a coagulant by determining concentrations at concentrations of 50, 75, 100 , 150 and 250 mg/l and stirring speed at 100, 120 , 130 , 140 and 150 rpm in each coagulant with the coagulation-flocculation (jartest) process. This experiment uses chitin powder and chitosan as primary coagulants whose test results are compared with alum synthetic coagulants. The water samples used in this research were taken from the raw water treatment systems. From the results of this study, the results obtained were 250 mg/l consentration chitin powder capable of reducing 53,1% turbidity at 130 rpm stirring speed and 150 mg / l concentration chitosan capable of reducing 62.8% turbidity at stirring speed 130 rpm.